2007
DOI: 10.1590/s1415-54192007000100007
|View full text |Cite
|
Sign up to set email alerts
|

Comparação de parâmetros periodontais após utilização de contenção convencional 3x3 plana e contenção modificada

Abstract: OBJETIVO: o presente estudo teve como propósito comparar os parâmetros periodontais após a utilização de dois tipos de contenções ortodônticas fixas: contenção convencional 3x3 plana (fio ortodôntico 0,8mm retilíneo fixado apenas nos caninos contralaterais) e a contenção modificada (fio ortodôntico 0,6mm com dobras permitindo o livre acesso do fio dental e fixado em todos os dentes do segmento anterior). METODOLOGIA: quinze voluntários primeiramente utilizaram a contenção convencional por seis meses. Após um i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 15 publications
1
12
0
11
Order By: Relevance
“…The results showed that there were statistically significant differences between the groups for PI, CAL and PD, showing an influence of the orthodontic bonded retainer on the periodontium. The results of this study showed that there was a greater accumulation of plaque in the test group compared to the control group, which was expected, because the presence of orthodontic bonded retainers hinders access to proper hygiene (5,11,(14)(15)(16). Similar results were reported by Artun et al (14), who found a greater accumulation of plaque in the interproximal surfaces of teeth with fixed bonded retainers when compared to teeth associated with removable retainers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results showed that there were statistically significant differences between the groups for PI, CAL and PD, showing an influence of the orthodontic bonded retainer on the periodontium. The results of this study showed that there was a greater accumulation of plaque in the test group compared to the control group, which was expected, because the presence of orthodontic bonded retainers hinders access to proper hygiene (5,11,(14)(15)(16). Similar results were reported by Artun et al (14), who found a greater accumulation of plaque in the interproximal surfaces of teeth with fixed bonded retainers when compared to teeth associated with removable retainers.…”
Section: Discussionsupporting
confidence: 87%
“…There is no way to predict which cases will present clinical relapses or when it might occur, so the duration of this phase is often unclear (9,11). It has been described in the literature that the biggest drawback in the use of fixed orthodontic bonded retainers is the difficulty of maintaining proper hygiene in the region, allowing for the accumulation of plaque and favoring the appearance of gingivitis and periodontal damage over time (5,(11)(12)(13)(14)(15)(16). There is a lack of studies evaluating the periodontal status of patients utilizing orthodontic bonded retainers for the lower incisors over a long period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Há uma tendência geral dos ortodontistas optarem pela contenção fixa, devido às dificuldades de adaptação, estética e ao movimento da língua que pode levar ao desajuste do aparelho removível. (SHIRASU et al, 2007) As contenções ortodônticas fixas são utilizadas em casos onde a instabilidade entre os dentes da arcada é prevista, sendo então necessário o uso de uma contenção prolongada. Elas são mais indicadas para os dentes ântero inferiores.…”
Section: Contenção Inferiorunclassified
“…2016) A maior desvantagem no uso de contenções ortodônticas fixas está na dificuldade de higienização dessas áreas, pois estas se tornam propícias ao acúmulo de placa bacteriana e consequentemente cálculo, podendo levar a inflamação gengival e maiores danos ao periodonto ao longo do tempo. (SHIRASU et al, 2007) Existe um maior risco de recidiva no segmento anterior, comparado ao posterior, sendo indicado o uso de uma contenção fixa inferior. Os fios multifilamentados e semiflexíveis têm capacidade de permitir os movimentos fisiológicos dos dentes, como também a sua superfície oferecer um aumento na retenção mecânica do adesivo.…”
Section: Contenção Inferiorunclassified
See 1 more Smart Citation